Exploring street graphics: Strategies and challenges for city branding in Kumasi, Ghana - Anane-Antwi, Eric; Nunoo, Francis Kofi Nimo; Marful, Alexander Boakye; Duah, Daniel Yaw Addai (Taylor and Francis, 2024)
Street graphics are the main feature of urban areas providing opportunities for advertising, wayfinding, visual stimulation, and other activities while adding to the quality of the urban area. Street graphics can potentially affect a city’s overall brand and appeal. Many cities are experiencing visual pollution as a byproduct of unregulated street graphics. Due to its unique categorisation as a historical and commercial centre, Kumasi, the second largest city in Ghana, provided the opportunity to investigate the use of street graphics for branding. The study through a constructivist-interpretive perspective approach, utilised visual survey and philology to gather data and analyse the street’s graphic composition and establish the reasons for its presence. It became obvious through the results of the study that the clatter of the street graphics has affected the process of identifying and agreeing upon a relevant set of city brand attributes Kumasi require. The mixture of street graphics which is strongly skewed towards Funerals, Religious programs, and Herbal Medicine, suggest that Kumasi may want to be identified with that but that is not the core objective of the City of Greater Kumasi Area. Kumasi does not seem to have a clear identity, although it is home to wonderful tangible and intangible cultural heritages (the Golden Stool and the Ashanti Kingdom). Although the city has seen significant structural development and modernization without any direction for identity, the managers of the city have not sought to define the identity of the city, and the street graphics have also compounded the identity crisis. An assessment criterion was developed to compare the various street graphics on the streets with recommendations regarding the type of street graphics employed and their overall effect on the host street that can have significant impact on its branding.